Spectrum of microbial infection in an Intensive Care Unit: a single centre tertiary care experience in Southern Indian state of Karnataka - S., Shruthi; Bhat, Balachandra S. (International Journal of Advances in Medicine, 2020)
Background: There is an increased incidence of hospital acquired infection, especially in ICU setting, the most common being ICU acquired pneumonia which increases the morbidity, mortality, prolongs hospital stay and consuming more resources. Microbial etiology of intensive care unit (ICU)-acquired pneumonia (ICUAP) determines antibiotic treatment and outcomes which vary from centre to centre. Hence, a study of risk factors, clinical profile of patient, microorganisms and their resistance patterns to antibiotics are important for the diagnosis, prognosis of patient with ICU acquired pneumonia and also in the prevention of the same. Methods: Patients with ICUAP confirmed microbiologically were prospectively compared according to identification of 1 (monomicrobial) or more (polymicrobial) potentially pathogenic microorganism. Patients without microbiological confirmation were excluded from the study. We assessed clinical characteristics, microbiology and outcome variables. Results: In the present study 60 patients with ICU Pneumonia were included out of which 50 (83%) had mono-microbial infection. Most common organism isolated in mono microbial infection was Klebsiella species (26%), followed by Acinetobacter species (25%), out of which 20 percent was multidrug resistant. Multi-drug resistance was similarly frequent in both groups. Outcome variables like initial response to the empiric treatment, length of stay and mortality were similar in both monomicrobial and polymicrobial pneumonia. Mortality rates were higher with higher pneumonia scores (p value <0.002) and with multi organ dysfunction (p <0.008) irrespective of mono microbial or poly microbial infection. Conclusions: In this study mono microbial infection was more than polymicrobial, the most common organism being Kliebsiella species followed by Acinetobacter species. When empiric treatment is frequently appropriate, mortality rates were higher with higher pneumonia scores and MODS. In our study polymicrobial aetiology did not influence the outcome of ICUAP.